1982
DOI: 10.1123/jsp.4.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Psychological Effects of Short-term Exercise Addiction on Habitual Runners

Abstract: This experiment examined, through quantitative measures, exercise dependence in subjects who had been running at least a year and ran at least 5 days a week. The subjects, 24 males and 9 females, were randomly assigned to groups according to the Solomon four-group design. Two groups ran and the other two did not on the day of the experiment. Pretests were given to one of the running and one of the nonrunning groups. Dependent variables were the Profile of Mood States (POMS) and galvanic skin response. Overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0
2

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 0 publications
0
28
0
2
Order By: Relevance
“…However, for some people, exercise can become an obsession, known as exercise dependence, defined as "a process that compels an individual to exercise in spite of obstacles, and results in physical and psychological symptoms when exercise is withdrawn". 1 Early research 2 on exercise dependence emphasised possible biological antecedents and medical consequences [3][4][5] for aerobic exercise, but little evidence has been presented on the motivational components of excessive exercise. 4 6-8 To date, most exercise dependence inventories have been aerobically based and unvalidated, 9 but much anecdotal evidence [10][11][12] indicates that people can become dependent on bodybuilding.…”
mentioning
confidence: 99%
“…However, for some people, exercise can become an obsession, known as exercise dependence, defined as "a process that compels an individual to exercise in spite of obstacles, and results in physical and psychological symptoms when exercise is withdrawn". 1 Early research 2 on exercise dependence emphasised possible biological antecedents and medical consequences [3][4][5] for aerobic exercise, but little evidence has been presented on the motivational components of excessive exercise. 4 6-8 To date, most exercise dependence inventories have been aerobically based and unvalidated, 9 but much anecdotal evidence [10][11][12] indicates that people can become dependent on bodybuilding.…”
mentioning
confidence: 99%
“…The most common symptoms reported include loss of energy, fatigue, tension, confusion, lower self-esteem, insomnia and irritability (Conboy, 1994;Harris, 1981;Robbins & Joseph, 1985;Szabo, 1995;Thaxton, 1982). However, the severity of these symptoms does not reach clinical significance.…”
Section: Withdrawalmentioning
confidence: 99%
“…The majority of injuries examined in the study were classified as "minor," which signified one week of non-participation in athletic endeavors. Thaxton (1982) conducted a study with 33 habitual runners. Half of the runners abstained from running for 24 hours while the other half maintained their usual schedule.…”
Section: Withdrawalmentioning
confidence: 99%
“…The most frequently reported symptoms of withdrawal were guilt, anxiety, depression, and irritability (Bamber, Cockerill, & Carroll, 2000;Szabo, Frenkl, & Caputo, 1997). It has been suggested that as little as 24 hours without exercise may be sufficient to produce significant withdrawal symptoms in some individuals (e.g., Sachs, 1981;Thaxton, 1982).…”
Section: Negative Reinforcement (Withdrawal Symptoms)mentioning
confidence: 99%
“…However, in a recent study attempting to delineate diagnostic criteria, withdrawal symptoms emerged as one of only two criteria implying dependence (Bamber et al, 2003). It has certainly been suggested that habitual exercisers may learn to rely on exercise to counteract anxiety or depression, control mood states, or lose weight, and that a subsequent inability to exercise results in negative psychological consequences in the form of withdrawal symptoms (Baekeland, 1970;Morris, Steinberg, Sykes, & Salmon, 1990;Thaxton, 1982).…”
Section: Negative Reinforcement (Withdrawal Symptoms)mentioning
confidence: 99%